A Mental Health Promotion Model through the Interaction of Social Capital and Javanese Cultural Values to Prevent Emotional Distress - Herdaetha, Adriesti (Journal of Nutrition and Public Health, 2025)
Background: Mental health is a vital component of holistic well-being, yet it often remains overlooked in public health strategies. Emotional distress, in particular, significantly impairs individual productivity and quality of life. In Javanese communities, especially in Surakarta, local cultural values and social capital present considerable potential as protective factors against mental health issues. Aims: This study aims to develop a mental health promotion model based on the interaction between social capital and Javanese cultural values to reduce emotional distress among adults. Methods: A sequential exploratory mixed-methods approach was employed. The qualitative phase explored local cultural values and social capital through interviews with key community figures, while the quantitative phase tested variable relationships using path analysis and Partial Least Squares-based Structural Equation Modeling (PLS-SEM). A total of 328 respondents aged 19–59 from Surakarta were selected through multistage random sampling. Validated instruments measured social capital, cultural values, self-efficacy, stress tolerance, coping strategies, risky behavior, and emotional distress. Results: The findings reveal that both social capital and Javanese cultural values have a significant negative correlation with emotional distress (r = -0.462 and r = -0.418, respectively). Path analysis confirmed that these variables influence emotional distress both directly and indirectly via mediators such as self-efficacy, stress tolerance, and coping strategies. Risky behavior was positively associated with emotional distress (β = 0.216). The highest scores were observed in social capital and self-efficacy, while risky behavior and emotional distress showed the lowest. Conclusion: The resulting model demonstrates the effectiveness of a community-based mental health promotion strategy rooted in local cultural wisdom and social engagement. It provides both theoretical and practical contributions by integrating socio-cultural dimensions into mental health promotion efforts, particularly in culturally rich settings such as Indonesia.